DINAMIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SEKOLAH DASAR - Hartati, Afiatun Sri (IAIN Ponorogo, 2015)
Abstract: The research revealsÂ the actualÂ issue PAIÂ learningÂ in SDN Gonggang 1 with the various problems that arise and attempt a solution. To answer this problem formulated the problem of how the implementation of learning and problems of anything that appears and attempts to solve it? The study used a qualitative approach to the subject of research is the PAI teachers and principals. Data collected by documents, observations andÂ interviews. EnterprisesÂ improveÂ the objectivity and credibility of the data andÂ interviews conducted withÂ triangulation repeats. Data were analyzed accordingÂ suggestion Miles and Huberman which consists of dataÂ reduction, data display, and verification or conclusion. The results showed: 1) In general, if based on the average value of classes for subjects PAI is good enough. 2) The problem that arises is the problem of classroom management, assessment, limited allocation of time, and the problem of interaction of teachers and pupils. To overcome the problems are: a) Teachers PAI need to establish a pattern of classroom management approach to socio-emotional climate, b) teachers need to use multiple assessment tools to assess studentsâ affective attitude that scale, questionnaires, interviews, observation and self refort.Â Ø£Ø´ÙØª ØªÙØ§ ÙÙØ§Ø´ÙØ§ ÙÙØªÙ Ø¹Ù Â Â Ù Ù ÙØ¹ØªÙØ§ PAI Ø©ÙÙØ¹ÙÙØ§ Ø©ÙÙØ´ÙØ§ ÙØ¹ ÙØ´ÙÙ Ø«ØØ¨ÙØ§Â Ø¡ÙØ´ ÙØ£ ÙÙØ§Ø´Ù Ù Ù ÙØ¹ØªÙØ§ Ø°ÙÙÙØª Ø©ÙÙÙÙ Ø©ÙÙØ´Ù ØªØ¹Ø¶Ù Ø©ÙÙØ´ÙØ§ ÙØ°Ù ÙÙØ¹ Ø©Ø¨Ø§Ø¬ÙÙ .ÙØ ÙØ¥ ÙØµÙØªÙØ§ Ø©ÙÙØ§Ù ÙÂ .Ø³Ø±Ø§Ø¯ÙØ§ ÙØ±ÙØ¯Ù Ù ÙÙ ÙØ¹ÙØ§ PAI ÙÙ Ø«ØØ¨ÙØ§ Ø¹ÙØ¶ÙÙ ÙØ¹ÙÙÙØ§ Ø¬ÙÙÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ØªÙ Ø¯Ø®ØªØ³Ø§ ØØ§ÙÙÙ ØªÙÙØ§Ù Ù ÙØ¯Ø¨ÙÂ Ø©ÙÙØ§Ø¯ØµÙ Ù Ø©ÙØ¹ÙØ¶ÙÙ ÙØ³Øª ÙÙØ¹ ØªØ§Ø³Ø³Ø¤ÙØ§ .ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§Ø¸ØÙÙØ§Ù ÙØ¦Ø§Ø«ÙÙØ§ ÙÙØ® ÙÙ Ø§ÙØ¹Ø¬ Øª ØªÙØ§ ØªØ§ÙØ§ÙØ¨ÙØ§Â ÙØ°ÙØ§ ÙØ§Ù Ø±Ø¨ÙÙÙ Ø²ÙÙØ§Ù ØØ§ØªÙØ§ Ø§ÙÙÙ ØªØ§ÙØ§ÙØ¨ÙØ§ ÙÙÙØª Øª Ø¯ÙÙ .Ø«ÙÙØ«ØªÙØ§ Ø±Ø§Ø±ÙØª Ø¹Ù ØªÙØ±Ø¬Ø£ ØªÙØ§ ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§ÙØ§ÙØ¨ÙØ§Â Ø§Ø°Ø¥ ØÙ Ø§Ø¹ ÙÙØ´Ø¨ )1 :Ø¬Ø¦Ø§ØªÙÙØ§ ØªØ±ÙØ¸Ø£ .Ø¬Ø§ØªÙØªØ³ÙØ§ ÙØ£ ÙÙØØªÙØ§Ù ØØªØ§ÙØ§ÙØ¨ÙØ§ Ø¶Ø±Ø¹Ù ØØªØ§ÙØ§ÙØ¨ÙØ§ ÙØ§Ø²ØªØ®Ø§ ÙÙ ÙÙÙØªÙÂ Ø£Ø´ÙØª ØªÙØ§ Ø©ÙÙØ´ÙØ§ ÙØ¥ )2 .Ø©ÙØ§ÙÙÙØ§ ÙÙÙ Ø§Ø¨ Ø¯ÙØ¬ ÙÙ PAI Ø©ÙØ³Ø§Ø±Ø¯ÙØ§ Ø¯Ø§ÙÙ ÙÙ ØªØ§ÙØ¨Ø·ÙØ§ Ø©Ù ÙÙ Ø·Ø³ÙØªÙ Ø³Ø§Ø³Ø£ ÙÙØ¹Â .Ø°ÙÙ ÙØªÙØ§Ù ÙÙ ÙØ¹ÙØ§ ÙØ¨ ÙØ¹Ø§ÙØªÙØ§ Ø©ÙÙØ´Ù Ù ØÙÙ Ø²ÙØ§ ÙÙ Ø©Ø¯ÙØ¯Ù ØµÙØµØªÙ ØÙ ÙÙÙØªÙ ØÙØµÙØ§ Ø©Ø±Ø§Ø¯Ø¥ Ø©ÙÙØ´Ù ÙÙÂ ÙØ¹Ø§Ù ØªØ¬ÙØ§ Ø®Ø§ÙÙ ÙÙ Ø©ÙÙØµÙØ§ Ø©Ø±Ø§Ø¯ÙØ§ Ø¬ÙÙ ÙÙ Ø·Ù Ø³ÙØ³Ø£Øª ÙØ¥ Ø©Ø¬Ø§Ø¨ PAI ÙÙ ÙØ¹ÙØ§ )Ø£ :ÙÙ ÙÙØ§Ø´ÙØ§ ÙÙØ¹ Ø¨ÙØºØªÙÙÂ Ø§Ø°ÙØ¨ ÙÙØ·Ø§Ø¹ÙØ§ Ø¨ÙØ·ÙØ§ ÙÙÙÙØ§ Ù ÙÙÙØªÙ Ø©Ø¯Ø¯Ø¹ØªÙ Ù ÙÙÙØª ØªØ§ÙØ¯Ø£ Ù Ø§Ø¯Ø®ØªØ³Ø§ ÙØ¥ Ø©Ø¬Ø§Ø Ù Ø©Ù ÙØ¹Ù Ù Ø§Ù ÙØ¹Ù )Ø¨ ØÙÙØ·Ø§Ø¹ÙØ§Ù.ÙØµÙØ§ Ø±ÙØ±ÙØªÙ Ø©Ø¸ØÙÙØ§Ù ØªÙØ¨Ø§ÙÙØ§Ù ØªØ§ÙØ§ÙØ¨ØªØ³ÙØ§Ù ØÙ Ø¬ÙØ§Kata Kunci: PAI, pembelajaran, problematika